Analisis Disparitas Pendapatan Pengusaha Sapi Perah Yang Berada Di Desa Pacet Kecamatan Pacet Kabupaten Mojokerto - Fitrah Barokah Qur’aini; Muhammad Yasin (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to determine the income disparity of dairy cattle entrepreneurs in Pacet Village, Pacet District, Mojokerto Regency. This research method uses a descriptive quantitative method using primary data, the data used is a questionnaire obtained from respondents of dairy cattle entrepreneurs. The data analysis tool in this study is the gini ratio. The results of this study can be explained that the total % of income in class in the first class is 0.86%, the second class is 0.14%, the third class is 0.20%, the fourth class is 0.26%, the fifth class is 0,32% with a total percent of income of 100%. And it can also be explained that there is cumulative income in the first class of 0.08%, the second class is 0.23%, the third class is 0.42%, the fourth class is 0.68% and the fifth class is 100%. Then, the value of the gini coefficient (gini ratio) using the five-class method is 0.232, it can be seen that the level of inequality of dairy cattle entrepreneurs in Pacet Village, Pacet District, Mojokerto Regency is in the category of low income inequality.